Epigenetic genome-wide association methylation in aging and longevity. (October 2012) - Ben-Avraham, Danny; Muzumdar, Radhika H; Atzmon, Gil
The aging phenotype is the result of a complex interaction between genetic, epigenetic and environmental factors. Evidence suggests that epigenetic changes (i.e., a set of reversible, heritable changes in gene function or other cell phenotype that occurs without a change in DNA sequence) may affect the aging process and may be one of the central mechanisms by which aging predisposes to many age-related diseases. The total number of altered methylation sites increases with increasing age, such that they could serve as marker for chronological age. This article systematically highlights the advances made in the field of epigenomics and their contribution to the understanding of the complex physiology of aging, lifespan and age-associated diseases.